2005
DOI: 10.1177/105382590502800106
|View full text |Cite
|
Sign up to set email alerts
|

Personal Learning or Prescribed Educational Outcomes: A Case Study of the Outward Bound Experience

Abstract: Experiential organizations often adopt quantitative course evaluation, as this provides them with numbers to justify prescribed educational outcomes to funding bodies. However, it has been argued that qualitative methods better suit the personal nature of the experiential learning process, so that epistemological understanding follows pedagogical philosophy (Allison & Pomeroy, 2000). This article highlights the learning of participants at Outward Bound New Zealand. A mixed method approach was chosen includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 19 publications
(36 reference statements)
2
32
1
1
Order By: Relevance
“…One key social dimension participants bring is ethnicity, although ethnic differences have rarely been investigated directly. Adventure programs have shown promising results across several nations including Singapore (Gassner & Russell, ; Wang et al., ), Australia (Gillespie & Allen‐Craig, ; Neill & Dias, ), New Zealand (Martin & Leberman, ; Somervell & Lambie, ), and South Africa (Draper et al., ). Furthermore, Glass and Benshoff () obtained no significant differences across ethnic groups (Caucasian, African American, and Hispanic) in the degree to which group cohesion developed from the beginning to the end of a U.S. adventure program.…”
Section: The Critical Programmatic Experiencesmentioning
confidence: 99%
“…One key social dimension participants bring is ethnicity, although ethnic differences have rarely been investigated directly. Adventure programs have shown promising results across several nations including Singapore (Gassner & Russell, ; Wang et al., ), Australia (Gillespie & Allen‐Craig, ; Neill & Dias, ), New Zealand (Martin & Leberman, ; Somervell & Lambie, ), and South Africa (Draper et al., ). Furthermore, Glass and Benshoff () obtained no significant differences across ethnic groups (Caucasian, African American, and Hispanic) in the degree to which group cohesion developed from the beginning to the end of a U.S. adventure program.…”
Section: The Critical Programmatic Experiencesmentioning
confidence: 99%
“…It also appears that similar to the unstructured nature of an EBWP, the participants are given the opportunity to take control and responsibility for their own process of growth. What was found by Martin and Leberman (2005) is accentuated by the majority of participants (78%) in this study: … the mere fact that it is here … it is much more peaceful and you do not need to think about all kinds of small things and nonsense … yes … it already just helps in this aspect. Immediately you also become more aware of yourself … you then pay more attention to yourself simply because now it is only you … and … therefore … you come to be aware of the whims and things about yourself and what actually probably bothered you and what it is you have to work at to improve.…”
Section: Solitudementioning
confidence: 60%
“…In this respect and with specific reference to centre-based team-building programmes and wilderness expeditions, Greffrath et al (2008) found in a comparative study that if significant personal development is sought, centre-based team-building programmes should be used. Martin and Leberman (2005) further accentuate the fact that if adventure experiential learning is to be understood, it would be necessary to move away from the use of quantitative research methods. To accurately interpret the meaning of this type of experience and to minimise generalisation, several researchers (Greffrath et al, 2008;Martin & Leberman, 2005) recommend that more qualitative research take place.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Connolly, Carns & Carns, 2005, Hatch & McCarthy, 2003Norton & Tucker, 2010) and that group cohesion opens up opportunities for the sharing of untold personal stories (e.g. Loeffler, 2005;Martin & Leberman, 2005). Gillis and Thomsen (1996) state that one of the important characteristics of adventure-based experiential learning is to transfer the learning that took place during the adventure experience to other life areas of participants.…”
Section: Cohesionmentioning
confidence: 99%